Genetic variations involved in interindividual variability in carotenoid status - Borel, Patrick (Molecular nutrition & food research, 2012)
As shown in most clinical studies dedicated to carotenoids, there is a huge interindividual variability in absorption, and blood and tissue responses, of dietary carotenoids. The recent discovery that several proteins are involved in carotenoid metabolism in humans has prompted a possible explanation for this phenomenon: genetic variants in genes encoding for these proteins may affect their expression or activity, and in turn carotenoid metabolism and carotenoid status. The proteins clearly identified so far are (i) the carotene oxygenases β,β‐carotene‐15,15′‐monooxygenase (BCMO1) and β,β‐carotene‐9′,10′‐oxygenase (BCDO2), which are involved in carotenoid cleavage, (ii) scavenger receptor class B type I (SR‐BI), cluster determinant 36 (CD36), and Niemann Pick C1‐like 1 (NPC1L1), which are involved in carotenoid uptake by cells, and (iii) glutathione S‐transferase Pi 1 (GSTP1) and human retinal lutein‐binding protein (HR‐LBP), which are involved in the transport of xanthophylls in the retina. Other proteins, such as ATP‐binding cassette subfamily G member 5 (ABCG5) and the fatty acid‐binding proteins (FABPs) are also apparently involved although firmer evidence is still required. A genome‐wide association study, as well as several candidate gene association studies, has shown that groups of subjects bearing different alleles in single nucleotide polymorphisms located in or near several of the above‐mentioned genes display different blood and/or tissue concentrations of carotenoids. Further studies are needed to identify all the proteins involved in carotenoid metabolism and assess whether other types of genetic variation, e.g. copy number variants and epigenetic modifications, can modulate carotenoid status. One potential application of such research could be personalized dietary guidelines for carotenoids according to individual genetic characteristics.